Decoupled Quorum-based Byzantine-Resilient Coordination in Open Distributed Systems - Bessani, Alysson Neves (2009)
Open distributed systems are typically composed by an unknown number of processes running in heterogeneous hosts. Their communication often requires tolerance to temporary disconnections and security against malicious actions. Tuple spaces are a well-known coordination model for this kind of systems. They can support communication that is decoupled both in time and space. There are currently several implementations of distributed fault-tolerant tuple spaces but they are not Byzantine-resilient, i.e., they do not provide a correct service if some replicas are attacked and start to misbehave. This paper presents an efficient implementation of LBTS, a Linearizable Byzantine fault-tolerant Tuple Space. LBTS uses a novel Byzantine quorum systems replication technique in which most operations are implemented by quorum protocols while stronger operations are implemented by more expensive protocols based on consensus. LBTS is linearizable and wait-free, showing interesting performance gains when compared to a similar construction based on state machine replication